2021
DOI: 10.1126/scitranslmed.aaz9705
|View full text |Cite
|
Sign up to set email alerts
|

Lithium preserves peritoneal membrane integrity by suppressing mesothelial cell αB-crystallin

Abstract: Life-saving renal replacement therapy by peritoneal dialysis (PD) is limited in use and duration by progressive impairment of peritoneal membrane integrity and homeostasis. Preservation of peritoneal membrane integrity during chronic PD remains an urgent but long unmet medical need. PD therapy failure results from peritoneal fibrosis and angiogenesis caused by hypertonic PD fluid (PDF)–induced mesothelial cytotoxicity. However, the pathophysiological mechanisms involved are incompletely understood, limiting id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 102 publications
(122 reference statements)
2
17
0
1
Order By: Relevance
“…We have previously shown that the addition of cytoprotective additives to PD fluid is a valid strategy to ameliorate the damage caused by PD fluids to peritoneal cells [ 11 , 18 , 23 , 24 , 25 , 26 ]. Alanyl-glutamine (AlaGln) has been described to counteract oxidative stress, so we next tested if it can ameliorate the observed effects of exposure of endothelial cells when added to double-chamber fluid (neutral pH).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that the addition of cytoprotective additives to PD fluid is a valid strategy to ameliorate the damage caused by PD fluids to peritoneal cells [ 11 , 18 , 23 , 24 , 25 , 26 ]. Alanyl-glutamine (AlaGln) has been described to counteract oxidative stress, so we next tested if it can ameliorate the observed effects of exposure of endothelial cells when added to double-chamber fluid (neutral pH).…”
Section: Resultsmentioning
confidence: 99%
“…PD introduces well-described vascular damage in the peritoneal membrane resembling diabetic vasculopathies [ 9 , 11 , 12 ]. The endothelial cells of these vessels function as the actual filter that regulates the peritoneal fluid transport during PD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PMCs play important roles in pathological conditions, such as peritoneal dialysis dysfunction [ 21 ], intra-abdominal adhesions [ 22 ], peritoneal inflammation, peritoneal tumor dissemination [ 23 ], and endometriosis [ 24 ]. PMCs also play key roles in dynamic regulation processes such as peritoneal repair [ 25 ], scarring [ 26 ], the regulation of macrophage migration [ 27 ], and the promotion of coagulation [ 25 , 28 ], including the formation of fibrin and the promotion of fibrinolysis [ 29 , 30 ].…”
Section: Anatomical Physiological and Pathological Features Of Pmcsmentioning
confidence: 99%
“…High-throughput omics technologies such as microarrays, RNA-sequencing, or proteomics methods allow for simultaneous measurements of thousands of molecular features and support elucidation of dysregulated processes in diseases along with the identification of molecular biomarkers and novel drug targets. A combined analysis of transcriptomics and proteomics data in the context of PD recently led to the identification of the beneficial impact of lithium on peritoneal membrane integrity, thus demonstrating that an integrated analysis of Omics data can also lead to novel therapeutic strategies [3]. A number of individual Omics studies in the context of PD have been published in the past couple of years investigating the impact of different dialysis fluids or different additives on patient outcome and the discovery of associated molecular pathways [4,5].…”
Section: Introductionmentioning
confidence: 99%